Development of a human-guided micro-manipulation system using touch-screen interface - Xiao, Xue (2019)
In the recent decades, in the field of micromanipulation for biomedical and material sciences, optical tweezer has played a significant role in facilitating the operation of research and development of technologies. Micromanipulation is a method of controlling microscopic objects using devices that enable users to move target objects that is so small to be manipulated with human’s capability. To increase human’s control over microscopic objects in the microscopic world, the objective of the project is to develop a human-guided micromanipulation system with the incorporation of a touch-screen interface. The micromanipulation system which is known as optical tweezer was programmed by LabVIEW. It will be controlled with a multi-touch interface wirelessly with Transmission Control Protocol (TCP) for data transmission. Real time data transfer of touch locations from the touchscreen program to the desktop’s LabVIEW program was achieved with minimal delay. Key phases of the projects are software development of the touchscreen application using Python, development of the data receiver with LabVIEW program so to control the optical tweezer machine. Finally, the testing of controlling action was carried out on a robotic arm where multi finger manipulation on two different joints simultaneously was achieved.